Patient Loyalty is Assessed from Service Response Time, Officer Competence, Health Facilities and Complaint Handling - Rahardi Rahardi; Istiatin Istiatin; Yunia Wahdiati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study to analyze the response time of staff competence, healthcare facilities and complaint handling in relation to patient loyalty at the Tawangsari Community Health Center in Sukoharjo Regency, both simultaneously and individually. This research method employs quantitative approach with a descriptive research design. The study population consists of outpatients at the Tawangsari Community Health Center in Sukoharjo Regency, with a sampling technique using the census method, resulting in a sample size of 120 patients. Data collection was carried out via a questionnaire. The data analysis techniques used included multiple linear regression, the F – test , t -test and the coefficient of determination. The research findings indicate that, both individually and collectively, the variables of service response time, staff competence, healthcare facilities and complaint handling have a significant impact on patient loyalty at the Puskesmas Tawangsari in Sukoharjo Regency. Therefore, it is recommended that the Puskesmas management improve service response times through innovation, enhance staff competence through training, maintain the quality of healthcare facilities, and ensure a more responsive and targeted complaint handling process, increasing patient loyalty.